Comparison between the Radiographic and Clinical Rates of Success for TheraCal and MTA in Primary Tooth Pulpotomy within a 12-Month Follow-Up: A Split-Mouth Clinical Trial. (19th April 2023) - Hassanpour, Sedigheh; Aminabadi, Naser Asl; Rahbar, Mahdi; Erfanparast, Leila
Abstract : Background . The present study was conducted for contrasting the efficacy of TheraCal and MTA for primary molar pulpotomy. Methods . During the current split-mouth randomized clinical trial, 90 bilateral primary molars from 45 healthy 5- to 8-year-old children were pulpotomized using TheraCal in one bilateral tooth and MTA in the other, randomly. Glass ionomer (GI) was used to cover these materials. Then, the treated teeth were restored with stainless steel crowns (SSC) and followed up clinically and radiographically at months 6 and 12 after treatment for any pulpotomy failure indications. Finally, data were analyzed by chi-square test considering p value < 0.05 as statistically significant. Results . Among 82 teeth available at the final follow-up session, the total success rates were 98.1% and 99.3% for TheraCal and MTA, respectively, showing no significant difference between the two groups (p > 0.05 ). Conclusion . TheraCal can be used as an alternative material for pulpotomy of primary teeth instead of MTA.